Serological evidence of Maedi-Visna and Caprine Arthritis Encephalitis in sheep and goats in the Korça region in Albania - Rezart, Postoli; Enkeleida, Ozuni; Dјadјovski, Igor; Anita, Koni; Sonila, Çoçoli; Kristi, Morava; Vera, Vasiliki; Koleci, Xhelil (German Multidisciplinary Publishing Center, 2023)
Lentiviruses infect small ruminants and cause similar but different two significant diseases: Maedi-Visna in sheep and Caprine Arthritis Encephalitis in goats. In the current study, 91 of 413 adult sheep and goats from the Korça region tested positive for small ruminant lentiviruses. Furthermore, 11 of the 25 small ruminant herds have at least one positive animal for small ruminant lentiviruses. The overall observed herd prevalence was 44.0% (95% CI: 29–59) for both diseases, 38.6% (95% CI: 18.6-55.1) for Maedi-Visna in sheep, and 66.7% (95% CI: 43.1-90.2) for Caprine Arthritis Encephalitis in goats. The average observed prevalence rate ranges from 20% to 82.9% (95% CI: 12–89.2) within positive goat’s herds, while within sheep-positive herds, it varies from 23.1% to 57.1% (95% CI: 11.7–70.4). There was a positive correlation between seroprevalence rate and animal species; goats seem to have an odd 2.36 (OR 95% CI: 1.48-3.76) higher than sheep to test positive in ELISA. Other risk factors, such as farm size, indoor versus outdoor rearing, and close farm biosecurity, may play a role in disease transmission between and within small ruminant animals’ herds. This is the first study on the prevalence of Maedi-Visna infection in sheep and one of the few published Caprine Arthritis Encephalitis studies in Albania. These findings support the presence of Small Ruminant Lentiviruses (SRLV) in the Korça district emphasize the need for monitoring and controlling SRLV infection in sheep and goats. According to the study’s conclusions, a yearly monitoring program is essential and must be developed in the future to keep the disease under control. This initiative aims to help owners understand SRLV and the need to raise seronegative animals